Evaluation of the Environmental Economic Performance of Carbon Exchange as an Emissions Trading Instrument in Indonesia - Jewel Kartika Putri Setiawan; Sri Astuti (Journal of International Conference Proceedings, 2024)
The carbon exchange is a regulatory system that governs Carbon Trading and maintains records of Carbon Unit ownership. This study empirically examines the influence of carbon intensity, tax avoidance, and macroeconomic stability on carbon disclosure. The population for this research consists of companies in the Mining, Petroleum, Agriculture, and Basic Industries and Chemicals sectors listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. Data collection involved accessing the official IDX website, www.idx.co.id, and the individual websites of the companies. Using the purposive sampling method, 132 samples were selected to ensure relevance and alignment with the study’s criteria. The research employs logistic regression analysis as the method of data analysis to assess the relationship between the independent and dependent variables. The findings reveal that macroeconomic stability positively influences carbon disclosure practices, while neither carbon intensity nor tax avoidance has a significant effect on carbon disclosure. These results contribute to understanding the factors that drive carbon disclosure and provide insight into the role of economic conditions in shaping corporate sustainability practices.